Black mamba boy - Mohamed, Nadifa 1981- (HarperCollins, 2010)
"Jama is ten years old and has grown up in the slums of this ancient city, learning to survive amongst the ragamuffins and vagabonds of the port. When he loses everything, his only chance of survival lies in finding his father who disappeared years before. So begins an epic journey by foot, camel, lorry and train, through war-torn Eritrea and Sudan, to Egypt, Palestine and, finally, to the icy realms of Britain that Jama heard about in Yemen. This story of one boy's journey is also the story of how the Second World War affected Africa and its people; a story of exile and survival and a vivid tale of love, friendship and boundless hope." Klappentext
Keywords: Geschichte; Orphans / Somalia / Fiction; Fathers and sons / Fiction; Somalia / History / Fiction; Fiktionale Darstellung